Electrohydraulic lithotripsy of gall stones--in vitro and animal studies. Issue 3 (March 1987) - Harrison, J; Morris, D L; Haynes, J; Hitchcock, A; Womack, C; Wherry, D C
Abstract : Electrohydraulic lithotripsy of human gall stones was investigated in vitro in a bath of saline and in a saline perfused bile duct. The technique was effective--only two stones could not be shattered. Electrohydraulic lithotripsy power requirement correlated with mechanical strength of stones, but not with biochemical composition. A trend toward higher power requirement was recorded with larger stones and stones over 2 cm in diameter could not be fragmented. Safety studies indicated that electrohydraulic lithotripsy was safe, provided the probe tip was not in contact with the bile duct wall. In vivo studies did not show any late effects after 10 days. Electrohydraulic lithotripsy is likely to be useful in the management of biliary calculi.